The Role of Surgery in Patients with COVID-19-Related Thoracic Complications - Raveglia, Federico; Scarci, Marco; Rimessi, Arianna; Orlandi, Riccardo; Rebora, Paola; Cioffi, Ugo; Guttadauro, Angelo; Ruffini, Enrico; Benvenuti, Mauro; Cardillo, Giuseppe; Patrini, Davide; Vannucci, Fernando; et al. (Frontiers in Surgery, 2022)
Objective: a number of thoracic complications induced by SARS-CoV-2 infection may benefit from surgery, but its role in this pathology is largely unknown and many surgeons advice against any surgical referral. Our aim was to investigate efficacy and safety of surgery in COVID-19 patients with thoracic complications requiring operation. Methods: we have designed an observational multicentre study, involving nine thoracic surgery departments, evaluating patients who developed in-hospital thoracic complications, surgically managed from 1 March 2020 to 31 May 2021. 30 days overall mortality was obtained by Kaplan-Meier. Multivariable Cox regression model and logistic models were applied to identify the variables associated with postoperative mortality and complications. Results: among 83 patients, 33 (40%) underwent surgery for complicated pneumothorax, 17 (20.5%) for pleural empyema, 13 (15.5%) for hemothorax, 8 (9.5%) for hemoptysis, 5 patients (6%) for lung abscess, 4 (5%) for infected pneumatoceles, 3 (3.5%) for other causes. At 30 days since surgery, 60 patients (72%) were alive. At multivariable analysis, age (HR 1.05 [95%CI: 1.01, 1.09], p=0.022), pulmonary hypertension (HR 3.98 [95%CI: 1.09, 14.5], p=0.036), renal insufficiency (HR 2.91 [95%CI: 1.19, 7.10], p value 0.019), thoracotomic approach (HR 4.90 [95%CI: 1.84, 13.1], p value 0.001) and infective affections (HR 0.17 [95%CI: 0.05, 0.58], p value 0.004) were found to be independent prognostic risk factor for 30-day mortality. Age (OR 1.05 [95%CI: 1.01, 1.10], p=0.023) and thoracotomy (OR 3.85 [95%CI: 1.35, 12.0] p=0.014) resulted to be significant predictor for 30-day morbidity. Conclusions: Surgical management of COVID-19-related thoracic complications is affected by high mortality and morbidity rates but 72% survival seems to be still satisfactory with a salvage intent. Younger patients, with no pulmonary hypertension, without renal insufficiency and undergoing surgery for infectious complications seem to have better prognosis.